Entrepreneurship education in China: Evidence from a preliminary scoping study of enterprising tendency in Chinese university students. Issue 2 (24th January 2020) - Liu, Tiantian; Walley, Keith; Pugh, Geoff; Adkins, Paul
Abstract : Purpose: The purpose of this study is to generate insight into the effects of entrepreneurship education in China by conducting a preliminary scoping study of the enterprising tendency of university students studying business. Design/methodology/approach: This study used a self-administered questionnaire based on the General Measure of Enterprising Tendency v2 (GET2) test to measure the enterprising tendency of a group of Chinese university students. Decision trees, using the Chi-square automatic interaction detector (CHAID) approach, and multiple regression analyses were used to investigate the enterprising tendency of respondents. Findings: The findings from this study indicate that the students have an overall medium level of enterprising tendency and strengths in some enterprising characteristics. The findings reveal that gender, family business, hometown and entrepreneurship education are significantly related to enterprising tendency but that age, household income, parents' education and occupation are not. Research limitations/implications: Although the study is based on a relatively small sample taken from just one university in Beijing, the findings suggest that the enterprising tendency of students can be encouraged by entrepreneurship education. Combined with evidence that entrepreneurship education is at a relatively early stage of development in China, this finding suggests considerable scope to increase student's enterprising tendency by extending, creating a more favourable environment for and improving the methods used to deliver entrepreneurship education. Enterprising tendency can be argued to naturally result in entrepreneurial intention; however, this extension is beyond the scope of this study, which is restricted to the analysis of enterprising tendency. Originality/value: This study makes an original contribution to knowledge as it is one of the first studies to explore enterprising tendency among university students in China. It has value for government, policymakers and university program designers in that it provides direction for entrepreneurship education in China.